A whole of population retrospective observational study on the rates of polypharmacy in New Zealand 2014 to 2018 Polypharmacy in New Zealand: What is the current status?. Issue 2 (10th March 2021) - Nind, James; Smith, Alesha; Devananda, Manjula; Auvray, Benoit
Abstract: Background and Aims: Polypharmacy (≥5 medicines) and hyperpolypharmacy (≥10 medicines) can significantly impact people's health. The literature surrounding polypharmacy focuses on the elderly, particularly rest home populations, with few studies looking into younger age bands. Moreover, there have been no recent studies looking into the rates of polypharmacy in New Zealand. This study aimed to determine whether polypharmacy rates have increased over time in the New Zealand population. Specifically investigating polypharmacy rates across age and ethnicity, and identifying which medicines are most commonly prescribed in people with polypharmacy. Methods: A nationwide retrospective observational study was carried out between 2014 and 2018 on 4 697 274 New Zealanders (96% of the population) by linking dispensing data from the Pharmaceutical Collection to patient enrolment data using a National Health Identifier (NHI) to identify the rate of long‐term medicine prescribing in New Zealand. Results: Our study found the rate of polypharmacy to be 9.93% and hyperpolypharmacy to be 1.92% nationwide in 2018, a percentage increase of 4.1% and 7.11% from 2014, respectively. During the same period, we observed the greatest percentage increase (30.37%) in the rate of polypharmacy in the 20 to 29 age band while the rates decreased in older populations. Variation was also noted between ethnicities. Medicines contributing to polypharmacy differed by age group. Conclusion: Current methods for minimizing polypharmacy and optimizing medicines use are narrowly focused on the elderly. Despite an increase in education and awareness raising campaigns, rates continue to rise in New Zealand's population.